Monkeypox: etiopathogenesis, prevention, and treatments - Hruby, Dennis (Henry Stewart Talks, 2022)
Monkeypox virus, Epidemiology, Modes of transmission, Viral structure and replication, virulence, Immune response, Vaccination, Therapeutic intervention, Anti-viral drug, Health surveillance, Clinical trial, Disease susceptibility, Disease prevention, Government policy